Theoretical and Economic-Legal Fundamentals of Financial Sustainability in the Example of Argo-Industry (Eurasian Journal of History, Geography and Economics, 2022)
This article describes the reform of agriculture in the country, in particular, the improvement of public administration in the sector, the widespread introduction of market relations, strengthening the legal framework of relations between producers, processors and sellers of agricultural products, attracting investment in the sector, introduction of resource-saving technologies and agriculture. The opinions of foreign and domestic scientists on the provision of manufacturers with modern equipment were discussed.